Compliant Mechanisms in Progress and Development Of Modern Technology - Lates, Daniel; Casvean, Marius (International Journal of Engineering and Management Sciences, 2020)
In this paper, the compliant mechanisms will be presented. There will be presented some representative works that have brought progress and development in modern technology. Examples will be presented from simple concepts such as a tweezers, staples, to mechanical clutches, pointer and micro-compliant mechanical structures.